QAZI AYAZ’S STYLE OF QURANIC COMMENTARY IN THE PERSPECTIVE OF HIS ARABIC WRITINGS - Dr. Ghulam Ahmad; Dr. Hafiz Mohammad Sarwar; Ume Habiba (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
Qazi Ayyaz is one of the famous scholars of the sixth century AH. He was simultaneously a commentator, narrator, writer, poet and orator. According to the descriptive method of this article, his scholarly status can be judged from the significant works in the field of Arabic explanation of Holy Quran. As the results, his leadership in the arena Arabic learnings been recognized in Arab genealogy and Arab existences.